FAVOURABLE CULTURE CONDITIONS FOR MYCELIAL GROWTH OF HYDNUM REPANDUM, A MEDICINAL MUSHROOM - Peksen, Aysun; Kibar, Beyhan; Yakupoglu, Gokcen (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
In this study, factors such as pH, temperature, carbon and nitrogen sources that affect mycelial growth of Hydnum repandum, a medicinal mushroom, were investigated. Different inoculum media for vegetative inoculum production were also examined. The best suitable pH for mycelial growth was found to be 5.5. Among constant temperatures, the best mycelial growth was obtained at 20 and 25°C. The mycelial growth drastically decreased at 15°C, and no mycelia were obtained at 30°C. Glucose and mannitol were found to be the most suitable carbon sources. Ca(NO 3 ) 2 as a nitrogen source gave the best results for mycelial growth. The poorest mycelial growth was noted in sucrose and xylose as carbon sources and in NH 4 NO 3 and (NH 4 ) 2 HPO 4 as nitrogen sources. Peat and peat: vermiculite mixtures (1:4, 1:6, 1:8 and 1:10, v:v) were the best media to use in producing the vegetative inoculum of H. repandum